Judicial oversight of the administration's actions in Iraq - Abbas Nasrallah; Nameer Ali Abdulwahab Ali Alobaidi (International Journal of Law Research and Studies, 2025)
The government has many different tasks, burdens and responsibilities that it must take care of, such as setting rules, providing services, and enforcing laws. Its job has become so complex that the government needs help to do all these things effectively. Therefore, it delegates, or grants, some of its powers to other organizations to assist it and make decisions on its behalf. These organizations "administer" the laws and policies of the government. The field of law that ensures that the government and its agencies deal with people fairly and legally is called administrative law.The research proposal in this article aims to analyze the legitimacy of the judiciary in its relationship with judicial administration, following a methodological path, at first, analyzing the importance of the administrative performance of the judiciary in the achievement and effectiveness of basic rights; then presenting the main lines for achieving the goal of this work in the end, which is to verify the existence of legitimacy in the aforementioned performance of the Iraqi judiciary. We will verify that the problem of the legitimacy of the judiciary lies outside the perspective of selecting administrative judges, and is not limited to scrutinizing judges, but rather involves adopting mechanisms of popular participation in managing the administrative work of the judiciary, which in fact is not limited to internal matters, but to the real activity of achieving important basic rights.
Keywords: Administrative Control; Management; Iraq